Geological evaluation of the Slovenian territory for radioactive waste disposal - Urbanc, Janko; Šinigoj, Jasna; Tomše, Peter (Geologija, 2002)
Due to the growing need for a final disposal of low and intermediate level (LILW) radioactive waste, the final solution for the short-lived LILW is one of the key issue of radioactive waste management in Slovenia at the moment. In the Area Survey Stage of the site selection process for the final disposal the suitability of the Slovenian territory for a surface or underground repository of LILW is examined by cabinet investigations in order to locate geologically suitable formations. The assessment of natural conditions of the system was based on consideration of the main geological, hydro-geological and seismotectonic conditions. It was performed with ARC/INFO technology. The results are compiled in a map, showing potential areas for underground and surface disposal of LILW in Slovenia. It has been established that there is a potential suitability for both surface and underground disposal on about 10,000 km2 of the Slovenian territory, which represents almost half of the entire Slovenian territory.